Guess what: It's the Settlements! - Thorsten Koeppl; Cyril Monnet (Queen's University, Department of Economics, 2005)
Exchanges and other trading platforms are often vertically integrated to carry out trading and settlement as one operation. We show that these vertical silos can prevent the full realization of efficincy gains from horizontal consolidation of trading and settlement platforms. Independent of the gains from such consolidation, when costs of settlement are private information, a merger of vertical silos cannot be designed to always ensure efficient trading and settlement after the merger. Furthermore, we show that efficiency can nevertheless be guaranteed either by delegating the operation of settlement platforms to agents or by forcing competition across vertical silos through cross-listings.
Keywords: C73; G20; G34; L22; 330; Clearing and Settlement; Cross-listing; Vertical and Horizontal Integration; Mechanism Design